WEB DESIGN INFORMATION USING JAVA PHP HOROSCOPES - Azizzulham Azizzulham; Melani Dewi Lusita, SKom, MMSI Melani Dewi Lusita, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Horoscopes Java application is a web application that contains information about themeaning of the date of birth by weton day (curiously), the phrase includes themeaning of the secret of life is the natural state at birth, affected by Batara (God) as inthe wayang, physical condition, typically, the bond of friendship , health, jobmatching, livelihood, hobbies and arranged marriages are packed in the form ofinteresting and interactive. This scientific authors describe how to make Web sitedesign using Microsoft's Java Horoscopes FronPage XP and supported by usingHTML, and PHP software. It is expected that applications can help a user who wantsto know the date of birth according to custom java as well as knowing the meaning ofthe date of birth.